Pengaruh Efektivitas Penerapan Standar Akuntansi Pemerintahan (SAP) dan Penerapan Sistem Informasi Pengelolaan Keuangan Daerah (SIPKD) Terhadap Kualitas Laporan Keuangan Pemerintah Kota Madiun Tahun 2021 - Rahmadhani, Iin; Hartono, Arif; Eka Ardiana, Titin (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to analyze the effect of the Effectiveness of Application of Government Accounting Standards (SAP) and Regional Financial Management Information Systems (SIPKD) on the Quality of Financial Reports for the Madiun City Government in 2021. This research is classified as a quantitative study. The population in this study were all secretaries and treasurers of the finance sub-section at the Madiun City SKPD office. The technique of determining the sample with Total Sampling, where the number of samples is equal to the population. The number of samples in this study were 52 respondents where the entire population was used as the research sample. The method of data analysis in this study is multiple linear regression analysis with the help of SPSS version 25. The partial results of the study show that the effectiveness of applying government accounting standards and regional financial management information systems has a significant positive effect on the quality of financial reports. Simultaneously the Effectiveness of Application of Government Accounting Standards and Regional Financial Management Information Systems has a significant positive effect on the Quality of Financial Reports. Keywords: Government Accounting Standards (SAP), Regional Financial Management Information System (SIPKD), Quality of Financial Reports